Serum gamma-glutamyl transferase: A novel biomarker for coronary artery disease - Mao, Yu (International Scientific Literature, Inc., 2014)
BACKGROUND: Atherosclerosis is a chronic inflammatory process, in which oxidative stress is the key event. Gamma-glutamyl transferase (GGT) is a cellular production of oxidants. We aimed to elucidate the relationship of serum GGT levels and coronary artery disease (CAD) in a Chinese population. MATERIAL/METHODS: A total of 513 adult subjects who had undergone coronary angiography were enrolled in the study. Clinical characteristics, coronary angiography, and serum samples were collected from all the patients and analyzed for the serum GGT, blood lipids, and cardiovascular risk factors. RESULTS: Subjects with CAD had significantly increased activity of serum GGT (p=0.003). Serum GGT levels exhibited positive correlations with alcohol intake (β=0.177, p<0.001), coronary complexity (β=0.068, p<0.001), and triacylglycerol (β=0.058, p<0.001). High-density lipoprotein cholesterol levels (β=0.157, p=0.008) and age (β=0.004, p=0.002) were negatively correlated with serum GGT in the CAD group. The coronary complexity presented a negative correlation with Ig-apolipoprotein AI (β=−2.517, p=0.001) and positive correlations with smoking (β=0.640, p<0.001), Ig-GGT (β=0.613, p=0.004), Ig high sensitivity-C reactive protein (β=0.320, p<0.001), and hypertension (β=0.286, p<0.026). CONCLUSIONS: The study showed a positive correlation between serum GGT and CAD in a Chinese population. Serum GGT levels may be a potential biomarker for CAD.